O amor em Kierkegaard: do amor erótico ao amor ao próximo - Paula, Marcio Gimenes de (Rapsódia, 2008)
The purpose of this article is analyses two moments of lovein Kierkegaard's works.The first moment is the erotic love, present in the interpretation about Socrate in Concept of irony and in the dialogue In Vino Veritas. The second momentis the interpretation about the christian love in the Works of Love. For to conclude will be some considerations about the Kierkegaard's ethics of love and his dialogue with the contemporary thought.